(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2025)
History of art shows many movements, trends, techniques and isms of arts in sequence. One trend departs from the other. This makes the new trend innovative, creative and aesthetic. Similarly, art theories and perspectives are also changing. The departure and transition bring new insights in the creator and viewers. Some trends, techniques and philosophy work for some period of time, and then there are transitions in between them. The transitions bring new forms and perspectives that provide new aesthetic experience. When same techniques and trends run for a long period, the artworks become stale, for there is only imitation and repetition. Successful artist breaks boundaries and goes beyond the established codes and rule of creation without sacrificing the aesthetic elements in his works. Thus, transition, change and departure are the essential elements of the arts. This research paper traces transitions and departure in art trends and aesthetics and presents the values of such transitions.